Assessment of weld joint strengths on dissimilar alloys of Inconel 625 and aluminium 7068 using FSW process. (2020) - Balasubramanian, M.; Stalin, B.; Marichamy, S.; Anandan, K.; Subbiah, Ram
Abstract: In recent welding techniques, friction stir weld has more advantages like good strength, no filler, and fusion of metal takes on the weld zone. Particularly, the dissimilar materials have been joined easily. The welding strength is a very essential factor to achieve the quality of welded joints. In the present concept, the two dissimilar alloys such as Inconel 625 and Al 7068 can be welded. The axial force, the spindle, and traverse speed were utilized as key factors. These key factors have affected the weld strength response factor. The role of factors and interaction is studied through the Pareto chart and analysis of variance. The optimal welding strength was attained by the Taguchi technique.